2022
DOI: 10.2196/27615
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Pediatric Teleconsultation to Prevent Skin Conditions in Infants and Reduce Parenting Stress in Mothers: Randomized Controlled Trial

Abstract: Background In Japan, eHealth for infants and mothers is currently an important aspect, but its effectiveness has rarely been examined. For infants, skin problems, including atopic dermatitis (AD), which is known to lead to other allergic diseases, are one of the most common conditions. Mothers of infants are prone to experiencing parenting stress, which adversely affects mothers’ and children’s well-being. Additionally, studies have reported that AD among offspring enhances parenting stress, and po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In particular, it should be noted that our results strongly reflected the trends among older adults; there was a lack of information on telehealth use among people enrolled in employee insurance (ie, the population of working age). Third, several studies have reported better outcomes in improving treatment adherence and preventing serious events with telehealth use [25][26][27]. Longer observation periods than in the present study would be needed to determine the incidence of events that could serve as medical outcomes; thus, this is a matter for future study.…”
Section: Limitationsmentioning
confidence: 86%
“…In particular, it should be noted that our results strongly reflected the trends among older adults; there was a lack of information on telehealth use among people enrolled in employee insurance (ie, the population of working age). Third, several studies have reported better outcomes in improving treatment adherence and preventing serious events with telehealth use [25][26][27]. Longer observation periods than in the present study would be needed to determine the incidence of events that could serve as medical outcomes; thus, this is a matter for future study.…”
Section: Limitationsmentioning
confidence: 86%
“…In particular, it should be noted that our results strongly reflected the trends among older adults; there was a lack of information on telehealth use among people enrolled in employee insurance (ie, the population of working age). Third, several studies have reported better outcomes in improving treatment adherence and preventing serious events with telehealth use [ 25 - 27 ]. Longer observation periods than in the present study would be needed to determine the incidence of events that could serve as medical outcomes; thus, this is a matter for future study.…”
Section: Discussionmentioning
confidence: 99%